2015
DOI: 10.1118/1.4914371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of film measurements and Monte Carlo simulations of dose delivered with very high‐energy electron beams in a polystyrene phantom

Abstract: The authors demonstrate that relative dose distributions for VHEE beams of 50-70 MeV can be measured with Gafchromic films and modeled with Monte Carlo simulations to an accuracy of 5%. The reported absolute dose differences likely caused by imperfect beam steering and subsequent charge loss revealed the importance of accurate VHEE beam control and diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Ḋ p was changed to four different values by adjusting the charge per pulse ( C p ) and no significant dose‐rate dependence was found. Similar conclusions were drawn by Bazalova et al in which the dose‐rate dependence of EBT2 for high energy electron beams was studied. In that work, a 60 MeV electron beam producing pulses of 1 ps length and a repetition frequency ( f ) of 1 Hz was used, and C p was varied between 17.5 and 53.0 pC in order to change Ḋ p from 3 × 10 12 to 9 × 10 12 Gy/s.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Ḋ p was changed to four different values by adjusting the charge per pulse ( C p ) and no significant dose‐rate dependence was found. Similar conclusions were drawn by Bazalova et al in which the dose‐rate dependence of EBT2 for high energy electron beams was studied. In that work, a 60 MeV electron beam producing pulses of 1 ps length and a repetition frequency ( f ) of 1 Hz was used, and C p was varied between 17.5 and 53.0 pC in order to change Ḋ p from 3 × 10 12 to 9 × 10 12 Gy/s.…”
Section: Introductionsupporting
confidence: 86%
“…As mentioned, the dose‐rate dependence of EBT3 film has only been investigated at very low Ḋ m (up to 6 Gy/min). Studies have been reported for other film types (EBT by Karsh et al and EBT2 by Bazalova et al), but many aspects were different in the irradiation conditions, such as w (1–5 ps vs. 1–2.2 μs in this study), beam energy (20 and 60 MeV vs. 4.9–6 MeV) and D p (much higher in this study). Most importantly, in our work Ḋ p was varied over a large range of several orders of magnitude over which no dose‐rate dependence was found.…”
Section: Discussionmentioning
confidence: 42%
“…Another limitation of the present study is the use of real clinical beam data for the simulation of the photon and proton fields used to generate the VMAT and PPBS plans while the VHEE data were taken from MC‐simulated beams. While the VHEE calculations have previously been validated experimentally on a 70 MeV beam line at SLAC National Accelerator Laboratory, no validation has been performed at the 100 and 200 MeV electron energies used in this study, and the VHEE beams represent a more idealized parameter space which was obtained from previous measurements from a high‐energy electron experimental beam line at NLCTA at SLAC National Laboratory …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, 16 equidistant coplanar beams with a beamlet size of 3 mm at full width at half maximum (FWHM) were used with a source to axis distance of 50 cm (assuming a bore size of 100 cm in diameter for the proposed machine design) (Table ). A beam emittance of 0.3 o was included in the VHEE beam simulations based on previous measurements obtained from a high energy electron experimental beam line at NLCTA at SLAC National Laboratory …”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that the MC dose was underestimated at both depths, which could potentially be attributed to the x‐ray tube end‐effect not accounted for in the MC simulations. Gafchromic films have been shown to be dose rate independent up to dose rates of 9 × 10 12 Gy/s …”
Section: Discussionmentioning
confidence: 99%